Cocaine Exposure and Children's Self-Regulation: Indirect Association via Maternal Harshness - Eiden, Rina; Schuetze, Pamela; Veira, Yvette; Cox, Elizabeth; Jarrett, Thomas; Johns, Josephine (Frontiers in Psychiatry, 2011)
Objectives: This study examined the association between prenatal cocaine exposure and children’s self-regulation at 3 years of child age. In addition to direct effects of prenatal cocaine exposure on children’s self-regulation, we hypothesized there would be indirect associations between cocaine exposure and self-regulation via higher maternal aggression and poor autonomic regulation in infancy. Methods: The sample consisted of 216 mother-infant dyads recruited at delivery from local area hospitals (116 cocaine exposed, 100 non-exposed). Infant autonomic regulation was measured at 7 months of age during an anger/frustration task, maternal aggression was coded from observations of mother-toddler interactions at 2 years of age, and children’s self-regulation was measured at 3 years of age using several laboratory paradigms. Results: Contrary to hypotheses, there were no direct associations between maternal cocaine use and children’s self-regulation. However, results from testing our conceptual model including the indirect effects via maternal aggression or infant parasympathetic regulation indicated that this model fit the data well, X2 (23) = 34.36, p > .05, Comparative Fit Index = .95, RMSEA = .05. Cocaine using mothers displayed higher intensity of aggression toward their toddlers during lab interactions across a variety of tasks at 2 years of age (β = .23, p < .05), and higher intensity of aggression at 2 years was predictive of lower self-regulation at 3 years (β = -.36, p < .01). Maternal cocaine use was also predictive of a non-adaptive increase in respiratory sinus arrythmia (RSA) from baseline to the negative affect task, but RSA change in infancy was not predictive of self-regulation at 3 years. Conclusions: Results are supportive of animal models indicating higher aggression among cocaine treated dams, and indicate that higher maternal aggression among cocaine using mothers is predictive of child self-regulatory outcomes over time.